La protection sociale et judiciaire de la jeunesse, premier pas vers une réforme globale du droit de la famille - Deleury, Edith; Rivet, Michèle (Les Cahiers de droit, 1978)
Two recent statutes adopted by the provincial Legislature will have considerable impact on the rights of children: Bill 24 replaces the Youth Protection Act and alters substantially the protection, both social and judicial, afforded to minors; Bill 65 replaces the concept of paternal authority of the Civil Code by that of parental authority. One cannot but laud the Legislator's intentions apparent in such statutory enactments but one must also note certain incoherent aspects of these recent laws. Thus, the reform of parental authority is much too limited and should have been carried out in the context of a complete revision of family law. As for the new Youth Protection Act, such a piece of legislation raises important questions concerning its implantation and application.